Studi Deskriptif Tidak Tercapainya Bonus Demografi di Kabupaten Landak - Panggabean, Meiran (Fakultas Ekonomi dan Bisnis, UNTAN, 2017)
This study aims to identify and analyze the cause of not achieving the demographic bonus in District of Landak from perspective of population-dynamics. To accomplish the study purposes, this study used the basic data from Population Census 2010 and used spectum program as the analysis tool. The conclusion showed that the cause of not achieving the demographic bonus is closely related to the high of fertility (TFR), the relatively low number of mortality (CDR, IMR and MMR) and negative net migration.